CRITICAL REVIEWS THE DEVELOPMENT OF SHARIAH STUDIES CASE IN IAIN RADEN FATAH - Hadi, Abdul (Nurani, 2014)
Abstract: Demands of quality is one major aspect, even this is not only required a change in IAIN UIN will be fixed but IAIN as it should also improve the quality of teaching disciplines. The emphasis includes three things, namely (a) the target character building (b) academic coaching, and (c) professional development. Character development in the Act on National Education System mentioned faith, piety and ethics; IAIN should have the device ready than most other universities. Based on research findings obtained by the conclusion that, at the Faculty of Shariah IAIN ongoing teaching-learning process tends to focus on the teaching of the normative approach. Curriculum that is not fully able to follow the dynamic developments. This is for example, the dominance of rote approach in teaching-learning process than the method of analysis and problem-solving. In the same time, any material provided more mature form of living things to swallow without the need to dismantle the ethos of science. Low professionalism, because IAIN no / less build reciprocal communication with the world market, particularly those related to the type produced profession. ملخص: مطالب من نوعية واحدة جانبا رئيسيا، وحتى هذا ليس مطلوبا تغيير في ايان UIN سوف تكون ثابتة ولكن ايان كما يجب أيضا على تحسين نوعية التعليم من التخصصات. التركيز يتضمن الأمور الثلاثة، وهما (أ) هدف بناء الشخصية (ب) التدريب الأكاديمي، و(ج) التطوير المهني. للتنمية الحرف في قانون نظام التربية الوطنية المذكورة الإيمان والتقوى والأخلاق، وايان يجب أن يكون الجهاز جاهزا من معظم الجامعات الأخرى. تستند إلى نتائج البحوث التي تم الحصول عليها عن طريق الاستنتاج بأنه، في كلية الشريعة ايان التعليم المستمر والتعلم عملية يميل إلى التركيز على تدريس النهج المعياري. المناهج الدراسية ليست قادرة تماما علىمتابعة التطورات الديناميكية. هذا هو على سبيل المثال، فإن هيمنة نهج التكرار في عملية التعليم والتعلم من طريقة التحليل، وعلى حل المشاكل. في الوقت نفسه، أي المواد التي قدمت أكثر نضجا شكل من أشكال الكائنات الحية على ابتلاع دون الحاجة لتفكيك أخلاقيات العلم. تدني الكفاءة المهنية، وذلك لأن أي ايان / أقل بناء الاتصال المتبادل مع السوق العالمية، ولا سيما تلك المتصلة نوع المهنة المنتجة. Kata Kunci: higher education, shariah, IAIN Raden Fatah.